Does metformin improve in vitro maturation and ultrastructure of oocytes retrieved from estradiol valerate polycystic ovary syndrome-induced rats. Issue 1 (December 2015) - Mesbah, Fakhroddin; Moslem, Mohsen; Vojdani, Zahra; Mirkhani, Hossein
Abstract Background Metformin decreases polycystic ovary syndrome (PCOS) symptoms, induces ovulation, and may improve developmental competence ofin vitro oocyte maturation. This study was designed to define the effects of metformin on the characteristics ofin vitro oocyte maturation in estradiol valerate (EV) PCOS-induced rats. Methods Forty-five adult female Sprague–Dawley rats were randomly divided into control; sham and PCOS-induced (treated by a single dose of estradiol valerate, 4 mg/rat, IM) groups. The body weight was measured weekly for 12 weeks. At the end of week 12, the serum levels of testosterone, estrogen, progesterone, LH, and FSH and blood glucose of all the rats were measured. About 380 cumulus oocyte complexes (control, 125; sham, 122; PCOS-induced rats, 133) were incubated in Ham's F10 in the absence and/or presence of metformin (M 5−10 ) for 12, 24, 36, and 48 h. The cumulus cells expansion and nuclear and cytoplasmic maturation of the oocytes was evaluated using 1 % aceto-orcein staining, and transmission electron microscopy (TEM). Results No significant differences were observed in the body weight of the rats. The serum level of testosterone was reduced, and progesterone and LH were significantly increased in the PCOS-induced rats (p < 0.05). However, no significant differences were observed in the serum levels of estrogen and FSH among the groups. Blood glucose level was higher in the PCOS-induced rats than control, (p < 0.01). The expansion of cumulus cells was observed in the metformin-treated oocytes. The oocytes retrieved from PCOS-induced rats show a stage of meiotic division (GVBD, MI, A-T, and MII) in 57.12 % of metformin-untreated and fairly significantly increased to 64.28 % in metformin-treated oocytes, (p < 0.05), but no differences were observed in the MII stage within groups. The redistribution of some cytoplasmic organelles throughout the ooplasm, particularly the peripheral cortical granules, was defined in the metformin-treated oocytes. Conclusions Single dose of EV can creates a reversible PCO adult rat model. Metformin enhances the COCs to initiate meiotic resumption at the first 6 h of IVM. In our study the metformin inability to show all aspects ofin vitro oocyte maturation and may be resulted from deficiency of EV to induce PCOS.